Regulation of epithelial sodium channels by cGMP/PKGII - Nie, Hong-Guang (Blackwell Science Inc, 2009)
Airway and alveolar fluid clearance is mainly governed by vectorial salt movement via apically located rate-limiting Na(+) channels (ENaC) and basolateral Na(+)/K(+)-ATPases. ENaC is regulated by a spectrum of protein kinases, i.e. protein kinase A (PKA), C (PKC), and G (PKG). However, the molecular mechanisms for the regulation of ENaC by cGMP/PKG remain to be elucidated. In the present study, we studied the pharmacological responses of native epithelial Na(+) channels in human Clara cells and human αβγδ ENaCs expressed in oocytes to cGMP. 8-pCPT-cGMP increased amiloride-sensitive short-circuit current (I(sc)) across H441 monolayers and heterologously expressed αβγδ ENaC activity in a dose-dependent manner. Similarly, 8-pCPT-cGMP (a PKGII activator) but not 8-Br-cGMP (a PKGI activator) increased amiloride-sensitive whole cell currents in H441 cells in the presence of CFTRinh-172 and diltiazem. In all cases, the cGMP-activated Na(+) channel activity was inhibited by Rp-8-pCPT-cGMP, a specific PKGII inhibitor. This was substantiated by the evidence that PKGII was the sole isoform expressed in H441 cells at the protein level. Importantly, intratracheal instillation of 8-pCPT-cGMP in BALB/c mice increased amiloride-sensitive alveolar fluid clearance by ∼30%, consistent with the in vitro results. We therefore conclude that PKGII is an activator of lung epithelial Na(+) channels, which may expedite the resolution of oedematous fluid in alveolar sacs.